1978
DOI: 10.4319/lo.1978.23.4.0752
|View full text |Cite
|
Sign up to set email alerts
|

Predicting particle selection by deposit feeders: A model and its implications 1

Abstract: A feeding model for a generalized, benthic deposit feeder is derived from a filter-feeding model and used to predict how such a deposit feeder would adjust its feeding to maximize its net energy gain. Under the assumption that deposit feeders are utilizing the bacterial fraction of the sediment or other surface organic coatings as food, the model predicts that the smallest particles should always be ingested, while the selection of larger particles depends on several parameters, including gut passage time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(73 citation statements)
references
References 23 publications
2
70
0
1
Order By: Relevance
“…They have not shown that the composition variable R has anything to do with nutritional value, however. If we assume, like Taghon et al (1978), that deposit feeders digest the microbiota on the surface of particles, the most meaningful nutritional parameter ought to be the surface:volume ratio of the ingested material. In these experiments, the animal could not be persuaded to ingest a sediment consisting entirely of glass spheres without added floc, and the surface: volume ratio of the latter is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They have not shown that the composition variable R has anything to do with nutritional value, however. If we assume, like Taghon et al (1978), that deposit feeders digest the microbiota on the surface of particles, the most meaningful nutritional parameter ought to be the surface:volume ratio of the ingested material. In these experiments, the animal could not be persuaded to ingest a sediment consisting entirely of glass spheres without added floc, and the surface: volume ratio of the latter is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Lehman (1976) and Lam and Frost (1976) have proposed models of planktonic filter feeding that depend heavily on the assumption that feeding behavior maximizes the net energy gain to the anirnal. Taghon et al (1978) have successfully adapted Lehman's model to deposit feeders. If these models are to have any predictive value, energetic considerations must be dominant over all the other selection pressures that might conceivably have shaped the morphology and behavior associated with feeding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This particulate material consists of an amorphous organic matrix surrounding clay and silt-sized mineral particles (< 88 pn) (see Zabawa, 1978, for a description of the physical properties of OMA). OMA are considered to be an important food resource to deposit feeders due to their high organic content (Johnson, 1974) and bacterial, meiofaunal, and microfloral associates (Hargrave, 1972;Taghon et al, 1978). OMA are major constituents of surficial sediments from the intertidal zone to depths of 5000 m (Johnson, 1977).…”
Section: The Study Areamentioning
confidence: 99%